“ABSURDITY” OF ALBERT CAMUS’ THE PLAGUE IN POLITICS OF PUBLIC HEALTH IN NIGERIA: DOUBTFUL TRUTHS AND TRUTHFUL LIES ONCOVID-19 PANDEMIC - Peter Akongfeh Agwu; George Ushie Kati (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2021)
Humanity has been hit in recent times, by unusual mortality provoked by the emergence of COVID-19. A report of 21 March 2020 by the Nigeria Centre for Disease Control (NCDC) confirmed 22 cases of the dreaded virus in the country. Desperate times they say require desperate measures. Facing the pandemic, the leadership of Nigeria has been more political than practical. Citizens resort to divers’ self-medication thus: Bathing with well-boiled Dogo Yaro leaves (Neem leaves); excessive consumption of bitter kola (Garcinia kola) or ginger (Zingiber) and the excessive consumption of alcohol. This study seeks to assess the level of preparedness by the Nigeria National Health System to combat the further spread of COVID-19 as apparently predicted in 1947 by Albert Camus in his work, The Plague. Our work further seeks to ascertain to what extent these self-aids have proven to be the effective panacea. It employs the conspiracy theory to argue that Nigerian leaders give priority to wealth accumulation over public health.